Impact of veno-venous extracorporeal membrane oxygenation on right ventricular impairment in severe ARDS: a prospective observational longitudinal study - Conrad, Alice; Dürschmied, Daniel; Bösing, Christoph; Thiel, Manfred; Beck, Grietje; Lücke, Thomas; Rocco, Patricia R.M.; Krebs, Jörg; Loosen, Gregor (Journal of intensive care medicine, 2025)
Purpose - Right ventricular impairment (RVI) can be alleviated by the initiation of veno-venous extracorporeal membrane oxygenation (V-V ECMO), which enhances gas exchange and allows for less invasive mechanical ventilation. However, the progression of RVI during V-V ECMO remains unclear. This study assesses echocardiographic changes in RVI over a five-day period in twenty acute respiratory distress syndrome (ARDS) patients with V-V ECMO support. - Material and Methods - Over a five-day period of V-V ECMO support, we examined echocardiographic markers of RVI, including right and left ventricular end-diastolic area ratio (RVEDA/LVEDA), tricuspid annular plane systolic excursion (TAPSE), tricuspid valve lateral anulus peak systolic velocity (S′), right ventricular fractional area change (FAC), and right ventricular myocardial performance index. Secondary objectives included changes in mechanical power transmitted to the respiratory system, hemodynamics and gas-exchange. - Results - RVEDA/LVEDA ratio remained elevated (0.8 [0.7-0.8] vs 0.7 [0.7-0.9]; p = .986), TAPSE decreased (2.0[1.6-2.5] cm vs 1.7 [1.4-2.2] cm; p = .024) while no changes were observed in S′ (16 [13-21] cm/s vs 15 [12-18] cm/s; p = .136) and FAC (38 [27-47] % vs 36 [29-43] %; p = .627). The right ventricular myocardial performance index improved (0.74 [0.45-1.00] vs 0.51 [0.42-0.80]; p = .004). Lung mechanical power was significantly reduced due to a decrease in lung elastic and resistive components. - Conclusions - Despite preserved longitudinal function and improved global performance, RVI persisted in severe ARDS patients on V-V ECMO, as indicated by the RVEDA/LVEDA ratio. These findings suggest that mechanisms beyond hypoxemia, hypercapnia and the invasiveness of mechanical ventilation contribute to RVI in these patients. - Trial registration - This trial was registered with the German Clinical Trials Register (DRKS00028584) on March 28, 2022. https://drks.de/search/en/trial/DRKS00028584
Gesehen am 25.09.2025